Dim Light at Night Increases Body Mass of Female Mice - Aubrecht, Taryn G. (Chronobiol Int, 2014)
During the past century the prevalence of light at night has increased in parallel with obesity rates. Dim light at night (dLAN) increases body mass in male mice. However, the effects of light at night on female body mass remain unspecified. Thus, female mice were exposed to a standard light/dark (LD; 16h light at ~150 lux/8h dark at ~0 lux) cycle or to light/dim light at night (dLAN; 16h light at ~150 lux/8h dim light at ~5 lux) cycles for six weeks. Females exposed to dLAN increased the rate of change in body mass compared to LD mice despite reduced total food intake during weeks five and six, suggesting that dLAN disrupted circadian rhythms resulting in deranged metabolism.